KARAKTERISTIK BAKTERI ASAM LAKTAT YANG DIISOLASI DARI SUSU KUDA SUMBA - Annytha Detha (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
The purpose of this study was to isolate and identify the lactic acid bacteria found in Sumba mares milk. This research will be carried out from September to November 2017 at the Veterinary Laboratory of the Livestock Service Office of East Nusa Tenggara Province. The research stages are isolation of lactic acid bacteria from Sumba mares milk by growing lactic acid bacteria on MRS agar media, and identifying lactic acid bacteria with gram staining, catalase test, motility test, and total plate count testing. Based on the results of the study, the presence of lactic acid bacteria originating from Sumba mares milk was characterized by the presence of colonies of lactic acid bacteria from Sumba mares milk which grew on MRS media agar as a selective medium for lactic acid bacteria. Based on the results of testing the characteristics of lactic acid bacteria Sumba mares milk has Gram positive, the negative results in the catalase test are characterized by not forming gas bubbles when the bacteria are added with H2O2. Based on the motility test obtained negative results or bacteria are non-motile and the number of lactic acid bacteria that can be a total picture of lactic acid bacteria that exist in Sumba mares milk in milliliter of milk. The conclusion are lactic acid bacteria isolated from Sumba mares milk has characteristic as Gram positive, basil or stem shaped, negative catalase and non motile, and has a total lactic acid bacteria of 3.5 x 108 cfu/ml (est).